(untitled) - Leeuwis, Cees (United Kingdom, 2002)
The main strength of GIS is the common analysis of compound spatial and attributive data. These later are collected by samples. The values of the collected type of data can be expanded to the sites where no samples are available using interpolation methods,...
Keywords: English language,Reading skill,Ngôn ngữ tiếng Anh,Kỹ năng đọc hiểu